Medium and long-term emergency department utilization after oesophagectomy: a population-based analysis. (10th April 2018) - Kidane, Biniam; Jacob, Binu; Gupta, Vaibhav; Peel, John; Saskin, Refik; Waddell, Thomas K; Darling, Gail E
Abstract: OBJECTIVES: Oesophagectomy is a complex operation with the potential for prolonged recovery. The aim of this study was to evaluate healthcare resource utilization, specifically emergency department (ED) visits within 1 year of oesophagectomy, and to identify risk factors for ED visits and frequent ED use (FEDU). METHODS: A retrospective cohort study of consecutive oesophagectomies for cancer in all Ontario hospitals was conducted using linked health data (2000–2012) including the ability to identify ED visits at non-index hospitals. Ontario has a single-payer healthcare system with a population of 13.8-million people. Multivariable regression was used to identify independent factors associated with ED visits and FEDU (≥3 ED visits) within 1 year after oesophagectomy. RESULTS: There were 3344 oesophagectomies with in-hospital mortality of 5.8% ( n  = 193). Of those discharged, 16.4% ( n  = 549), 36.0% ( n  = 1203) and 55.8% ( n  = 1866) had ED visits within 30 days, 90 days and 1 year, respectively. Higher comorbidity [adjusted odds ratio (aOR) = 1.08, 95% confidence interval (CI): 1.05–1.11, P  < 0.0001], rurality (aOR = 1.40, 95% CI: 1.10–1.78, P  = 0.006) and receipt of chemotherapy and/or radiation therapy (aOR = 2.55, 95% CI: 2.12–3.08, P  < 0.0001) were independent risk factors for ED visits within 1 year of oesophagectomy. Thoracoscopic-assisted surgery was independently associated with decreased ED visits (aOR = 0.67, 95% CI: 0.45–0.99, P  = 0.049). Eight hundred and thirteen (24.3%) patients had FEDU. Higher comorbidity (aOR = 1.11, 95% CI: 1.08–1.14, P  < 0.0001), rurality (aOR = 1.66, 95% CI: 1.31–2.10, P  < 0.0001) and receipt of chemotherapy and/or radiation therapy (aOR = 2.38, 95% CI: 1.93–2.93, P  < 0.0001) were independent risk factors for FEDU. One health region had more ED visits ( P  = 0.04) and more FEDU ( P  = 0.001) when compared with the other regions. There were higher ED visits and FEDU in the later years of the study period (both P  < 0.0001). CONCLUSIONS: ED visits are common after oesophagectomy with almost 25% of patients having ≥3 visits and >50% having ≥1 visit within 1 year of oesophagectomy. We have identified demographic, surgical and regional risk factors for the potential targeted quality improvement.